Konsep Penyelamatan dalam Pandangan Paulus - John Gratias Pakulayuk; Petrus Bine Saramae; Hendrik Palimbo (Departement of Mathematics Education, 2021)
Our human life in this world ends in death. The mystery of this death becomes a scary thing. However, for those who believe in God in Christ, death is the path to complete salvation. Sin causes humans to experience death. However, through Jesus Christ, God saved mankind from the destruction of death. It does not mean that humans will not die, but after going through death, God provides complete salvation.